The nature and legal status of the contract to connect a private solar energy system to the public electricity distribution system - Ahmed, Zhalin Fryad Ahmed; Hussein, Dr. Zubair Mustafa Hussein (Sulaimani Journal for Humanities, 2025)
Determining the nature and legal classification of the contract to connect a solar energy system to the public electricity distribution system is an important topic for determining the applicable law and rules for this contract in the event of a dispute between the two parties. This contract connects the energy produced by the producer's or investor's solar panels to the state's distribution networks, in exchange for a fee paid by the state to the producer or investor. In this research, we will discuss the nature and legal classification of this contract, whether it is considered an administrative or a civil contract, and what the appropriate classification of this contract is.
Keywords: contract to connect a solar energy system to the public electricity distribution system; administrative contract; civil contract; sales contract; contracting contract; supply contract